1986
DOI: 10.1104/pp.82.3.813
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Acyltransferase in Maturing Oil Seeds of Maize and Other Species

Abstract: Diacylglycerol acyltransferase (EC 2.3.1.20) activity was detected in the microsomal fractions of maturing maize scutellum, soybean cotyledon, peanut cotyledon, and castor bean endosperm. The activity detected was high enough to account for the in vivo rate of triacylglycerol synthesis. The activity of the maize enzyme was characterized using diolein micelles prepared by sonication in Tween 20 as the substrate. The activity was highest at pH values of 6 to 7. The activity was proportional to the amount of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…The coating of nascent oil bodies with oleosins is mediated by a cotranslational insertion of the oleosins into the ER membrane (59,86). This hypothesis was also confirmed by the localization of TAG biosynthesis enzymes at special subdomains of the ER (26,77,79,118).…”
Section: Nonprokaryotic Lipid Bodiessupporting
confidence: 60%
“…The coating of nascent oil bodies with oleosins is mediated by a cotranslational insertion of the oleosins into the ER membrane (59,86). This hypothesis was also confirmed by the localization of TAG biosynthesis enzymes at special subdomains of the ER (26,77,79,118).…”
Section: Nonprokaryotic Lipid Bodiessupporting
confidence: 60%
“…Previous in vitro experiments demonstrated that DGAT enzyme activity was associated with microsomal membrane preparations ( Figure 3) (Cao and Huang, 1986;Settlage et al, 1995;Lacey and Hills, 1996). To perform a more detailed investigation of the subcellular properties of these enzymes in plant cells, we expressed myc epitope-tagged tung DGAT1 or DGAT2 in tobacco BY-2 suspension cells and then examined their immunofluorescence staining patterns by confocal laser-scanning microscopy (CLSM).…”
Section: Dgat1 and Dgat2 Proteins Are Enriched In Subdomains Of The Ermentioning
confidence: 99%
“…This fraction may represent ER subdomains for TAG and oleosin synthesis, or simply fragments of ER regions originally closest to the budding OBs and thus have more TAGs and a lower buoyant density. In an earlier experiment, when an extract of maturing maize kernel was subfractionated by density gradient centrifugation, DAG AT, the last and unique enzyme for TAG synthesis, was found with cytochrome reductase in RER fragments of diverse buoyant densities (Cao and Huang, 1986); the DAG AT was not concentrated in ER fragments with the lowest buoyant densities and therefore most TAGs (or fewer polysomes). Thus, in the maize kernel cells, TAGs are likely synthesized in diverse regions of the ER and diffuse to the budding OBs.…”
Section: Er and The Synthesis Of Oils Oleosins And Obsmentioning
confidence: 99%